Pelatihan Teknologi Sterilisasi dalam Kemasan Plastik Tahan Panas untuk Memperpanjang Umur Simpan Sate Ayam Khas Ponorogo - Tjahja Muhandri; Ninuk Purnaningsih; Harum Fadhilatunnur; Subarna Subarna (Institut Pertanian Bogor, 2024)
Chicken satay is one of the signature dishes from Ponorogo Regency, often used as souvenirs by travelers. However, its short shelf life has limited the marketing and distribution area of the product. The activity aimed to train small enterprise partners in Ponorogo Regency to preserve their chicken satay using a simple commercial sterilization method and to measure the thermal process adequacy. The thermal process adequacy measurement was carried out at the SEAFAST Center, while the training was conducted in person at the partner's locations in Ponorogo. A questionnaire was distributed during the training to assess the participant's understanding of preserving food products using the thermal process. The sterilization process was performed by heating chicken satay in a pressure cooker for 1 hour (calculated since the maximum pressure cooker's temperature was reached), resulting in F0 values ranging from 4.2 to 5.2 minutes. The training was delivered by providing theoretical and practical experience. Data from questionnaires showed that the training improved the participants' understanding, with the average score per participant increased from 6.13 to 10.92 (32% increase).